1999
DOI: 10.1093/ajcn/69.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hearing loss, vitamin B-12, and folate in elderly women

Abstract: Background: Hearing impairment is 1 of the 4 most prevalent chronic conditions in the elderly. However, the biological basis of age-related hearing loss is unknown. Objective: The objective was to test the hypothesis that agerelated hearing loss may be associated with poor vitamin B-12 and folate status. Design: A thorough audiometric assessment was conducted in 55 healthy women aged 60-71 y. Hearing function was determined by the average of pure-tone air conduction thresholds at 0.5, 1, 2, and 4 kHz and was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
4
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 32 publications
6
87
4
6
Order By: Relevance
“…Findings like this suggest that cognitive contributions to hearing might be strengthened by vitamin use. Houston et al [1999] found that hearing thresholds were inversely correlated with serum vitamin B 12 and red cell folate in older women, suggesting that poor vitamin B 12 and folate status may be associated with age-related auditory dysfunction. However, in an analysis of blood samples taken from 91 subjects with presbycusis, Berner et al [2000] found no correlations between B 12 or folic acid levels and hearing sensitivity for pure tones or speech.…”
Section: Vitaminsmentioning
confidence: 94%
“…Findings like this suggest that cognitive contributions to hearing might be strengthened by vitamin use. Houston et al [1999] found that hearing thresholds were inversely correlated with serum vitamin B 12 and red cell folate in older women, suggesting that poor vitamin B 12 and folate status may be associated with age-related auditory dysfunction. However, in an analysis of blood samples taken from 91 subjects with presbycusis, Berner et al [2000] found no correlations between B 12 or folic acid levels and hearing sensitivity for pure tones or speech.…”
Section: Vitaminsmentioning
confidence: 94%
“…Ultimately, after a lifetime of noise exposure, it is difficult to distinguish between NIHL and ARHL, audiometrically as well as anatomically. Additional environmental factors, such as ototoxic substances, drugs or even diet, can influence susceptibility to ARHL [29][30][31]. Aminoglycoside antibiotics can damage hair cells in the same pattern as noise, causing a non-reversible HL predominantly affecting high frequencies.…”
Section: Non-genetic Components Of Presbycusismentioning
confidence: 99%
“…Along with heart problems, hypertension and arthritis the hearing impairment is one of the four leading chronic health conditions experienced by the elderly people. 1,2 It is characterised by an age dependent decline of auditory function associated with loss of sensory hair cells, spiral ganglion neurons and stria vascularis cells in the cochlea of inner ear. 3 It is also associated with difficulty in speech discrimination and central auditory processing of information.…”
Section: Introductionmentioning
confidence: 99%